MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DI SMP ISLAM ATTARBIYYAH DENGAN MODEL TWO STAY TWO STRAY: Improving Learning Outcomes of Islamic Religious Education at SMP Islam Attarbiyyah using Two Stay Two Stray Model - Nurjanah; Rara Siska; Teddy Suhardi; Nur Aini Farida; M. Makbul (TA'LIMUNA: Jurnal Pendidikan Islam, 2025)
Learning is a conscious effort to create a learning atmosphere that allows students to actively develop their potential. The learning process cannot be separated from the right method to achieve optimal learning outcomes. Therefore, innovative methods such as the Two Stay Two Stray (TSTS) type cooperative learning model are needed to improve student learning outcomes. The TSTS model is a learning model that provides opportunities for students to learn to solve problems, together with their group members; then exchange information with other group members. This article is the result of a Classroom Action Research (PTK) designed in two cycles. Each cycle consists of four stages, namely Planning, Acting, Observing and Reflecting. The findings are that in Cycle I, student learning outcomes have not reached learning completeness, then in Cycle II, student learning outcomes have reached learning completeness. Pembelajaran adalah usaha sadar untuk mewujudkan suasana belajar yang memungkinkan siswa secara aktif mengembangkan potensi dirinya. Proses pembelajaran tidak lepas dari metode yang tepat untuk mencapai hasil belajar yang optimal. Oleh karena itu, metode yang inovatif seperti model pembelajaran kooperatif tipe Two Stay Two Stray (TSTS) diperlukan untuk meningkatkan hasil belajar siswa. Model TSTS merupakan model pembelajaran yang memberikan kesempatan kepada siswa untuk belajar memecahkan masalah, bersama anggota kelompoknya; lalu saling bertukar informasi dengan anggota kelompok lainnya. Artikel ini merupakan hasil dari Penelitian Tindakan Kelas (PTK) yang didesain dalam dua Siklus. Masing-masing Siklus terdiri dari empat tahap, yaitu Perencanaan, Pelaksanan, Pengamatan dan Refleksi. Temuannya adalah pada Siklus I, hasil belajar siswa belum mencapai ketuntasan belajar, kemudian pada Siklus II, hasil belajar siswa sudah mencapai ketuntasan belajar. Kata Kunci : Hasil Belajar; Pendidikan Agama Islam; Pembelajaran Kooperatif; Two Stay Two Stray.